2016
DOI: 10.1111/dme.13288
|View full text |Cite
|
Sign up to set email alerts
|

FUT2 non‐secretor status is associated with Type 1 diabetes susceptibility in Japanese children

Abstract: The FUT2 gene contributed to the development of Type 1 diabetes in the present cohort of Japanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…While most studies have investigated a link between age at menopause and cardiovascular outcomes, reporting an increased risk of CVD associated with early onset of menopause, few studies have examined a possible association between age at menopause with risk of type 2 diabetes [ 3 ]. Cross-sectional studies examining the association between age at menopause and type 2 diabetes have yielded contradictory results, showing either no association or an increased prevalence of type 2 diabetes in women who experience early onset of menopause [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While most studies have investigated a link between age at menopause and cardiovascular outcomes, reporting an increased risk of CVD associated with early onset of menopause, few studies have examined a possible association between age at menopause with risk of type 2 diabetes [ 3 ]. Cross-sectional studies examining the association between age at menopause and type 2 diabetes have yielded contradictory results, showing either no association or an increased prevalence of type 2 diabetes in women who experience early onset of menopause [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, because the outcome (type 2 diabetes incidence) was assessed prospectively, the subjective measure of age at natural menopause would probably lead to non-differential misclassification with respect to the outcome, and would therefore bias estimates toward the null. Furthermore, previous reports indicate that the validity and reproducibility of self-reported age at menopause is fairly good [ 3 , 45 ]. In addition, mean age at natural menopause in the current study is similar to the mean age at natural menopause reported by other studies in the Netherlands and United States [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to genetics, environmental etiologies have not been validated and thus do not currently contribute to subject stratification in T1D prevention trials. However, some examples of gene-environment interactions include the interactions of the microbiome with the Fut-2 nonsecretor gene polymorphism, which increases risk of T1D and is associated with faster progression of presymptomatic T1D [10][11][12] , and interactions of picornaviruses, which include enteroviruses, with polymorphisms of the innate immunity viral RNA receptor gene region IFIH1(MDA-5) [13,14] .…”
Section: Introductionmentioning
confidence: 99%